Biodistribution of TNF-αα-coated gold nanoparticles in an in vivo model system. (June 2009) - Goel, Raghav; Shah, Neha; Visaria, Rachana; Paciotti, Giulio F; Bischof, John C
Aim: In this study, we describe the biodistribution of CYT-6091, a colloidal gold (Au)-based nanomedicine that targets the delivery of TNF-αα to solid tumors.Materials & methods: A single intravenous injection of CYT-6091 coated with 5 µµg TNF-αα was given to human prostate tumor-bearing or naive (without tumor) nude mice. Tissues were harvested and analyzed at specific time points for Au nanoparticles by atomic emission spectroscopy and TNF-αα by ELISA.Results: The two constituents of CYT-6091, TNF-αα and Au, exhibited different behavior in blood, with TNF-αα showing a faster decay than the Au nanoparticles. Between 0 and 4 h after injection, TNF-αα showed a preferential accumulation in the tumor. Au was observed to accumulate preferentially in the liver between 4 and 12 h, and showed some clearance over time (4 months).Conclusion: These data suggest that CYT-6091 delivers TNF-αα preferentially to the tumor and that upon TNF-αα degradation, the liver takes up Au, which is cleared slowly over time.